ANALISA KINERJA KEUANGAN SEBELUM DAN SESUDAH STOCK SPLIT PADA PT. BANK CENTRAL ASIA - Daris Purba; Asih Purwana Sari; V. Ade Arianto CP; Suratman Suratman; Rina Rina (JURNAL CAFETARIA, 2023)
The stock split by PT Bank Central Asia in October 2021 is expected to improve the company's financial performance. However, the sample shows that the RoA a year before and the year after the stock split does not show significant difference. Previous research has shown that stock splits do not necessarily affect financial performance. This study seeks to determine differences in financial performance at PT Bank Central Asia between before and after the stock split. The hypothesis of this study is that there are differences in the performance of the corporation before and after the stock split. This study used quantitative methods with 8 samples before the stock split and 8 samples after the stock split. The hypothesis testing used is paired t-tests. The conclusion of this study shows that the stock split done by PT Bank Central Asia in October 2021 made a significant difference to the company's financial performance afterwards.